Antibiogram and Biofilm Development among Klebsiella pneumoniae from Clinical Isolates (Tribhuvan University Journal of Microbiology, 2021)
Objectives: This study was aimed to evaluate antibiotic resistance pattern and biofilm formation in K. pneumoniae strains isolated from different clinical specimens and to study on association of drug resistance pattern with biofilm formation.Methods: A total of 944 clinical samples from patients attending Sahid Gangalal National Heart Center were processed from September 2019 to March 2020 to identify possible bacterial pathogens following standard microbiological procedures. K. pneumonaie isolates were further subjected to antibiotic susceptibility testing using modified Kirby Bauer disc diffusion technique. Biofilm formation was evaluated by tissue culture plate technique.Results: Of the total 944 samples, 15.47% (146) samples showed bacterial growth, among which 23.97% (35) were K. pneumoniae. Out of 35 K. pneumoniae isolates, 45.71% (16) were multidrug-resistant and 42.86% (15) were extensively drug-resistant. Sixty percent (21) of K. pneumoniae feebly produced biofilm. Significant association was observed between biofilm production and exhibition of multidrug resistance (p value